Burkholderia Gladioli – A Predictor of Poor Outcome in Cystic Fibrosis Patients Who Receive Lung Transplants? A Case of Locally Invasive Rhinosinusitis and Persistent Bacteremia in a 36-Year-Old Lung Transplant Recipient with Cystic Fibrosis. Issue 4 (2011) - Quon, Bradley S; Reid, James D; Wong, Patrick; Wilcox, Pearce G; Javer, Amin; Wilson, Jennifer M; Levy, Robert D
Abstract : There have been very few reports describing postlung transplant outcomes in patients' infected/colonized with Burkholderia gladioli pretransplant. A case involving a lung transplant recipient with cystic fibrosis who ultimately died as a result of severe rhinosinusitis due to B gladioli infection in the context of postlung transplant immunosuppression is reported.